Women's Economic Empowerment Based on Waste Bank Management to Improve Economic and Psychological Well-Being in Tourist Alleys: Pemberdayaan Ekonomi Perempuan Berbasis Manajemen Bank Sampah Untuk Meningkatkan Ekonomi da Psikologis Well Being pada Lorong Wisata - Wulan Purnamasari; Ika Wisudawaty; Israwaty Hamsar; Sri Hutami Adyningsih; Andi Tenri Ampa (Yayasan Ahmar Cendekia Indonesia, 2025)
This community service programme aims to empower Women Farmers Groups (KWT) through creative economy training and improving the professionalism of waste bank management in tourist alley areas. The background to this is the low income of KWT due to the sale of raw waste without added value and unstructured waste bank management, resulting in a lack of financial transparency. The programme aims to improve the welfare of KWT members while promoting sustainable waste management. The implementation method consists of three main stages: 1) Waste Bank Management Training, 2) Waste-Based Creative Economy Training, and 3) Digital Marketing and Partnerships. The programme lasts for six months, combining intensive training with mentoring. The expected outcomes are an increase in KWT members' income, a reduction in the volume of waste in tourist alleys, and the establishment of independent and professional waste banks. Long-term impacts include improved family economics, cleaner and more attractive tourist lanes to support eco-tourism, and KWT independence in managing the environment and creating business opportunities. With a participatory approach, this programme creates green jobs and aligns with several Sustainable Development Goals (SDGs). Abstrak Program layanan masyarakat ini bertujuan untuk memberdayakan Kelompok Wanita Tani (KWT) melalui pelatihan ekonomi kreatif dan meningkatkan profesionalisme pengelolaan bank sampah di kawasan lorong wisata. Latar belakang program ini adalah pendapatan rendah KWT akibat penjualan limbah mentah tanpa nilai tambah dan pengelolaan bank sampah yang tidak terstruktur, yang mengakibatkan kurangnya transparansi keuangan. Program ini bertujuan untuk meningkatkan kesejahteraan anggota KWT sambil mempromosikan pengelolaan limbah yang berkelanjutan. Metode implementasi terdiri dari tiga tahap utama: 1) Pelatihan Pengelolaan Bank Sampah, 2) Pelatihan Ekonomi Kreatif Berbasis Sampah, dan 3) Pemasaran Digital dan Kemitraan. Program ini berlangsung selama enam bulan, menggabungkan pelatihan intensif dengan pembimbingan. Hasil yang diharapkan meliputi peningkatan pendapatan anggota KWT, pengurangan volume sampah di lorong-lorong wisata, dan pembentukan bank sampah yang mandiri dan profesional. Dampak jangka panjang meliputi perbaikan ekonomi keluarga, lorong-lorong wisata yang lebih bersih dan menarik untuk mendukung ekowisata, serta kemandirian KWT dalam mengelola lingkungan dan menciptakan peluang bisnis. Dengan pendekatan partisipatif, program ini menciptakan lapangan kerja hijau dan sejalan dengan beberapa Tujuan Pembangunan Berkelanjutan (SDGs).